Implementasi Platform Digital Artificial Intelligence (AI) sebagai Media Pembelajaran Desain Grafis untuk Mengetahui Respon Siswa Desain Komunikasi Visual di SMKN 1 Japara - Sulaeman, Ibnu; Mahpudin, Asep (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to implement Artificial Intelligence (AI) digital platforms as a learning medium for graphic design to foster innovative ideas among students in the Visual Communication Design (DKV) program. The research method employed is qualitative with a descriptive approach, focusing on social reality by examining experiences as the primary data for understanding that reality. The primary focus of this research is to assess students' responses to AI as a learning medium for graphic design. The subjects of the study are 27 students from class XI DKV 1 and 27 students from class XI DKV 2, totaling 54 respondents. The data collected shows an average evaluation score of 80%, which falls into the